The Lambda stenting technique: a new approach to address EUS-guided biliary drainage–associated adverse events - Hiroki Sato, MD, PhD; Hidemasa Kawabata, MD, PhD; Mikihiro Fujiya, MD, PhD (VideoGIE, 2024)
Background and Aims: EUS-guided biliary drainage (EUS-BD) has been performed increasingly worldwide, especially in patients with malignant tumors in which ERCP is difficult, patients with surgically altered GI tracts, and older patients who are at high risk for surgery. EUS-BD requires high-level skills and has limited options for managing adverse events, particularly when stent migration and cholangitis occur. Adverse events, such as persistent bile leakage from the fistula and continuous reflux from the GI tract, are believed to always have a risk of severe exacerbation that could threaten the patient’s life. Methods: We encountered 2 cases of stent migrations and 1 case with repeated cholangitis in patients with malignant tumors among the patients who underwent EUS-BD. The migrated stent was visualized under EUS in 2 patients with stent migration, and an EUS-guided FNA needle was used to puncture the mesh of the stent. The cannulation catheter was directly inserted into the mesh of the stent in 1 case with repeated retrograde cholangitis, while the stent was visualized with an endoscope. Subsequently, a guidewire was inserted through the puncture site, and a second metal stent was deployed between the meshes of the first stent, bridging the GI wall again (Lambda stenting technique). All procedures were performed with the patient under general anesthesia, and the patients safely completed the intervention. Results: Patients’ conditions significantly improved after the second stent insertion, allowing for chemotherapy resumption while maintaining their activities of daily living. The second stent remained in place without any migration, and the stent successfully prevented further cholangitis. Conclusions: The Lambda stenting technique is considered highly effective for managing stent migration and repeated cholangitis, which is a major EUS-BD adverse event. This procedure helps avoid more invasive surgeries when stent migration and cholangitis occur and contributes to expanding EUS-BD applicability.